2014
DOI: 10.1158/1055-9965.epi-14-0462
|View full text |Cite
|
Sign up to set email alerts
|

The Cytokinesis-Blocked Micronucleus Assay as a Strong Predictor of Lung Cancer: Extension of a Lung Cancer Risk Prediction Model

Abstract: Background There is an urgent need to improve lung cancer outcome by identifying and validating markers of risk. We previously reported that the cytokinesis-blocked micronucleus assay (CBMN) is a strong predictor of lung cancer risk. Here we validate our findings in an independent external lung cancer population and test discriminatory power improvement of the Spitz risk prediction model upon extension with this biomarker. Methods 1,506 participants were stratified into a test set of 995 (527 cases /468 cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 39 publications
2
22
0
Order By: Relevance
“…In the BP-treated group, the shapes of the nuclei were altered together with the disruption of nuclear envelope and lamina. This may be correlated with the formation of micronuclei as be evident in the micronucleus assay (9). Mitochondria were found to be swollen, elongated and filled with flocculent material, giving a denser appearance.…”
Section: Discussionmentioning
confidence: 92%
“…In the BP-treated group, the shapes of the nuclei were altered together with the disruption of nuclear envelope and lamina. This may be correlated with the formation of micronuclei as be evident in the micronucleus assay (9). Mitochondria were found to be swollen, elongated and filled with flocculent material, giving a denser appearance.…”
Section: Discussionmentioning
confidence: 92%
“…Recently, this model was extended to incorporate micronuclei in binucleated cells (BN-MN) (OR 16.72 per unit increase, 95% CI 9.01-31.02) alongside environmental tobacco smoke exposure (OR 1.12, 95% CI 0.47-2.68) and a family history of cancer in two or more first-degree relatives (OR 1.06, 95% CI 0.47-2.43). 21 The average difference in BN-MN between cases and controls in the model's development and validation datasets was 1.78-1.79 units. 21 Assuming the ORs of the model variables closely approximate the RRs and an increase of 1.80 units of BN-MN compared to a never-smoker at average risk is considered, the model considers RRs up to at least 35.73 for never-smokers.…”
Section: Methodsmentioning
confidence: 94%
“…21 The average difference in BN-MN between cases and controls in the model's development and validation datasets was 1.78-1.79 units. 21 Assuming the ORs of the model variables closely approximate the RRs and an increase of 1.80 units of BN-MN compared to a never-smoker at average risk is considered, the model considers RRs up to at least 35.73 for never-smokers.…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…Examining a subset of cases and controls from their original study, Spitz et al found their models for former and current smokers performed better when adding two host DNA repair capacity markers (AUCs, 0.68 and 0.70) [33]. El-Zein et al [34] likewise extended the original smoking-stratified Spitz models by adding a cytokinesis-blocked micronucleus assay endpoint, which substantially improved prediction in a small external validation sample (AUC, from 0.61 to 0.92). Due to the case-control design, however, it is not entirely clear whether these markers reflect underlying causes or effects of lung cancer.…”
Section: Predicting Lung Cancer Risk Prior To Screening Initiationmentioning
confidence: 99%